0203 Lessons Learned From Relying On Team Dynamics To Prioritize Sleep Incollegiate Athletes. (27th April 2018) - Maguire, K; MacLea, D; Wilder, J N; Lisman, P; Dobrosielski, D; Burke, T; Capaldi, V; Yarnell, A; Brager, A
Abstract: Introduction: It is well established that sleep is a key determinant for performance optimization and injury prevention. Despite this knowledge, collegiate athletes have insufficient sleep relative to their physiological needs. Here, we aim to reduce homeostatic sleep debt and optimize rhythm stability of rise times/bed times in collegiate athletes by reliance on team dynamics in a long-term field study. Our aims were several-fold. Methods: First, we measured sleep/activity cycles across the preseason and entire (~ 12-weeks) competition season in women's (n=33) and men's (n=46) lacrosse and football teams (n=96). Second, we distributed personalized sleep reports that provided: a) individualized metrics of sleep quantity/quality; b) a comparison of individual sleep metrics to the entire team and specific positions (e.g., offense vs. defense); and c) the extent of cognitive alertness (or impairment) based on total daily sleep amounts. We also gave an educational seminar with the intent of enhancing personal responsibility for adequate sleep hygiene and to get athletes to 'buy in' to prioritizing sleep. Results: Throughout each sports season, we saw an unfortunate decrease in the extent of compliance. For lacrosse, initial compliance was ~ 85 ± 3% (W) and 84 ± 3% (M) but precipitously dropped to ~40% (W\M) by the end of the season (p=0.001, both). We have yet to determine how homeostatic sleep needs and rhythm stability of rise times/bed times in tactical (collegiate) athletes correlate with physiological, physical, and mental performance metrics, including heart rate variability, weight-bearing exercise, and on-the-field mental errors. Conclusion: Although this study is one of few studies to provide real-time feedback on sleep and performance outcomes in tactical athletes as part of a long-term field study, compliance statistics show the constant need for engagement and education with such field studies. Support (If Any): Department of Defense Military Operational Medicine Program